(Re)conceptualising precarity: institutions, structure and agency. Issue 3 (3rd April 2017) - Hardy, Jane Ann
Abstract : Purpose: The purpose of this paper is to reflect on the notion of precarious work and addresses the temporal, historical and analytical weaknesses manifest in many accounts by proposing a political economy synthesis. Design/methodology/approach: The discussion takes place through a political economy theoretical lens that takes seriously the structures and institutions of capitalism and the agency of workers individually and collectively. Findings: The paper concludes that precarious work is intrinsic to capitalism and therefore the precariat cannot be understood as a class-in-itself. The implications of this for activists are that solidarity needs to be forged between all groups of workers in order to organise for decent and stable employment. Originality/value: First, it is argued that two key structural influences on precarity are the spatiality of capitalism and its endemic tendency to crisis. Second, temporal and institutional "shapers" of precarity are discussed in historical and comparative context. Third, the agential influence on precarity is examined with regard to the possibility of the self-organisation precarious workers and their potential for forging solidarity with other groups.